Neutralizing VHH Antibodies Targeting the Spike Protein of PEDV - Li Zhang; Wei Miao; Mo Zhou; Miao Lin; Changyao Fu; Zhi Wu; Xinnuo Lei; Jialong Xu; Shinuo Cao; Shanyuan Zhu (Veterinary Sciences)
Porcine epidemic diarrhea virus (PEDV) is a highly contagious coronavirus that infect pigs’ intestinal epithelial cells, causing high morbidity and mortality. Due to the rapid mutation of PEDV, vaccine efficacy is uncertain, prompting exploration of alternative treatments. Nanobodies, also known as variable heavy chain domains of heavy chain-only antibodies (VHHs), offer significant potential in biomedical applications due to their small size and high specificity. In this study, yeast two-hybrid technology was employed to screen for eight specific VHH sequences targeting the PEDV S protein from a synthetically constructed nanobody yeast library. The VHH genes were then cloned into expression plasmids for recombinant protein production, and the resulting VHHs (termed PEDV S-VHHs) were purified. Indirect immunofluorescence assay (IFA) and Western blotting analysis confirmed that these VHHs specifically bind to both PEDV and its S protein. Neutralization assays demonstrated that seven PEDV S-VHHs exhibited potent neutralizing activity against PEDV. Additionally, a combination of these seven antibodies showed enhanced antiviral effects. Preliminary predictions were also made regarding the binding sites between these VHHs and PEDV. The PEDV S-VHHs described in this study hold potential as candidates for the prevention and treatment of PEDV infection.